(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Fire is one of the most serious disasters that threaten public safety and a major cause of damage to property, injury, and loss of life. It is important to know and be aware of the basic safety precautions and relevance of fire prevention to reduce or eliminate the occurrence of fire by training in fire safety, as well as in the proper maintenance and care of fire protection and life systems and by counting potential ignition sources and fuels. It was discovered that the respondents are ages 20 - 25 and above, the majority of them are aware of practicing basic safety precautions in the relevance of fire prevention, and the children playing with fire is one of the main causes why fire incidents occurred in the community based on the knowledge of respondent in Brgy San Agustin. The problem encountered by the respondents is human error, which means that untrained staff or anyone can easily place combustible materials in the wrong place, which can cause fire incidents.